ANALISA PEMANFAATAN PROXY SERVER SEBAGAI MEDIA FILTERING DAN CACHING PADA JARINGAN KOMPUTER - Yuisar Yuisar; Liza Yulianti; Yanolanda Suzantri H (Jurnal Media Infotama, 2015)
This research aims to Implement control and safe use of the internet at an agency with a utilization fee seminal may use the Linux operating system Ubuntu 14:04. Bandwidth division according to the time of busy servers and Internet client. To quick opening for the second time and so on. Blocking sites - porn site that tends to contain spyware. Accelerate video audio streaming. This study uses experimental research. In this study conducted experiments on the performance of the proxy server that runs on the Linux operating system ubuntu 14:04 server. The results of subsequent experiments documented for analysis to produce appropriate recommendations for the creation of a proxy server. From the results of this analysis will be to get conclusions about the benefits and functionality in more detail from the proxy server, especially in the caching and filtering functions on the proxy server. The results of this study it appears that the proxy server is already running in accordance with the wishes of the authors expect and can access the Internet, the client of the proxy server can also access the internet. To block a specified website author, proxy servers can block websites with the HTTP protocol, while for a website that uses the HTTPS protocol proxies can not be blocked unless all websites that use the HTTPS protocol is also on the block. So in this study the authors simply block any website with the HTTP protocol. In this study blocked web is http://www.youtube.com.Keywords: Proxy Server, Filtering, caching, networking